Treatment of Iatrogenic Aortocoronary Arteriovenous Fistula with Coronary Covered Stent - Ender Ornek; Harun Kundi; Emrullah Kiziltunc; Mustafa Cetin (Case Reports in Cardiology)
An 83-year-old man, who underwent coronary artery bypass operation of left internal mammary artery (LIMA) to left anterior descending (LAD) artery, with sequential saphenous vein to the first and second obtuse marginal (OM) branches of circumflex artery 5 years ago and coronary artery stent implantation to right coronary artery 2 months ago, was admitted to the hospital with syncope and chest pain. Aortosaphenous graft selective angiography revealed that first sequential side to side ligation was inadvertently anastomosed to left posterolateral coronary vein with resultant flow into the coronary sinus and distal end to side sequential anastomosis to OM 2 coronary artery which was filling very weakly. In order to close this iatrogenic coronary arteriovenous fistula and to supply saphenous vein flow to OM artery, we decided to implant a graft covered stent into the saphenous vein at the same session.